Monetary sector model for Nigeria - Central Bank of Nigeria, Research Department (Abuja, Nigeria Central Bank of Nigeria, 2012)
The study aims at building a monetary sector model that would complement and serve as input to the maintenance of the macro model as well as aid projection of key macroeconomic indicators through simulation of impact of policy changes.
Includes bibliographical references.
oif 30/05/17
Ref.
Keywords: Macroeconomics; Monetary policy --- Econometric models; Nigeria